El Domo de la Roca: la ideología tras el símbolo - Cisneros, Fernando (El Colegio de México, 2017)
The Dome of the Rock —Qubbat al-Sakhra in Arabic— represents the monument of Islamic art which in recent years has been the subject of the most studies. The present article emphasizes the significance of its location, for the site where it is built represents in and of itself a symbolic reference which can be seen as a part of the point of view of the material aspects or composition as an artistic work, but is also part of its significance for different social groups, as a changing reference through different epochs, analized with reference to the concept of “dominion of memory” issued by Foucault.